The Influence of Social Media Marketing and Consumer Trust on the Purchase Decision at Suteki Sushi Restaurant Surabaya - Muji Utomo; Sengguruh Nilowardono; Miftahur Rochman (LPPM NAROTAMA UNIVERSITY, Indonesia, 2022)
The purpose of this study was to evaluate the impact of social media marketing and consumer trust on purchase decisions at Suteki Sushi Restaurant in Surabaya. Data was obtained by distributing questionnaires using a Likert scale via google form. The sampling technique used was purposive sampling with 100 respondents selected as Instagram users. The data analysis techniques used were descriptive analysis and verification analysis, namely: Validity Test, Reliability Test, Classic Assumption Test Multiple Regression Analysis, Coefficient of Determination Analysis (R2) and Hypothesis Testing with Partial Test (t test) and Simultaneous Test (F test). The findings of the test and analysis are as follows: There is a significant and favorable correlation between consumer trust and purchase decision with hypothesis testing obtained t-count 5.295 > t-table (1.985). Social media marketing has an unfavorable and small impact on purchase decisions, with hypothesis testing obtained t-count 0.604 < t-table (1.985). Social media marketing and consumer trust have a large and profitable impact simultaneously on purchase decisions with hypothesis testing obtained by Syg. 0.000 < 0.05.